Lactic Acid Bacterium Population Dynamics in Artisan Sourdoughs Over One Year of Daily Propagations Is Mainly Driven by Flour Microbiota and Nutrients - Minervini, Fabio; Dinardo, Francesca R.; Celano, Giuseppe; De Angelis, Maria; Gobbetti, Marco (Frontiers in Microbiology, 2018)
This study aimed to: (i) assess at what extent traditional, daily propagated, sourdough can be considered a stable microbial ecosystem; (ii) ascertain the drivers of stability/variability. For this purpose, samples of sourdough, flour and environment were collected over 1 year from three different bakeries located in Altamura, Castellana Grotte, and Matera. Culture-dependent and –independent analyses were carried out on all the samples. In addition, sourdough and flour were subjected to biochemical characterization. In all the sourdoughs sampled at the same bakery, cell density of lactic acid bacteria fluctuated of one-two log cycles. However, 16S metagenetic analysis showed that sourdough bacterial microbiota was remarkably stable, in terms of species. Yet, some differences were found during time at intra-specific level. Indeed, bacterial strains succeeded in a 1-year lapse of time or even in 6-months, such as in the case of strains isolated from Altamura sourdough samples. Residual carbohydrates, lactic acid, ethanol and free amino acids varied in the same sourdough collected at different sampling times. These variations could be attributed to combination of various factors, such as fermentation temperature and strain succession. In addition, concentration of flour nutrients varied over 1 year and, in some cases, in a shorter time lapse. This may have favored certain strains over others. For this reason and also because of its inherent contamination by lactic acid bacteria, we found flour as the major driver of strains succession.